Clinical Efficacy and Safety of Long-Term Compression in Patients with Mixed Arterial and Venous Etiology Ulcers in the Leg - Elhomsy, Sophie; Chrusciel, Jan; Sanchez, Stéphane; Elhomsy, Paul; Guillaumat, Jérôme (International Journal of Angiology, 2021)
Elastic compressions are standard treatment for leg ulcers of venous etiology. The effect of compressions on ulcers of mixed (arterial or venous) etiology, however, has rarely been studied. The objective of this study was to evaluate the variation in transcutaneous oxygen pressure (TcPO2) in patients with ulcers of mixed arterial or venous etiology treated with 1 month of compression. This prospective cohort study was conducted at a university hospital in France. Patient eligibility was for those attending a consultation of a work-up of a leg ulcer of mixed arterial-venous etiology lasting at least 4 to 6 weeks. Compressions were prescribed according to the hemodynamic status and were evaluated by the ankle-brachial index and toe-brachial index using a decision-making algorithm based on French national guidelines. Quality of life was assessed using the Short-Form 36-Item (SF-36) questionnaire. In total, 32 patients were included between September 30, 2018 and May 31, 2019. A difference was observed between TcPO2 before compression (49.3 ± 13.01 mm Hg) and after 1 month (51.2 ± 15.05 mm Hg), average change 1.9 ± 2.04 mm Hg (p = 0.025). The average ulcer size prior to compression was 49 ± 102 cm2 versus 37 ± 94 cm2 after 1 month of effective compression, corresponding to a reduction of 12 ± 8 cm2 (p < 0.001). There was a reduction in the bodily pain dimension of the SF-36. Compressions adapted to the hemodynamic status led to an increase in TcPO2, a reduction in wound size, and an improvement to bodily pain in patients with leg ulcers of mixed arterial-venous etiology.
Keywords: peripheral artery disease; wound care; mixed-etiology leg ulcers; compression; TcPO2